Agricultural Extension on Broiler Chicken Farm Management to Enhance Employee Capacity and Youth Interest - Diding Bajuri; Sasigaran Moneyam; Fitria Mar'atul Janah; Imas Yani Filtriani; Arie Nurfauzi; Galur Gumelar Tito; Adhytia Rizki Alfandi; Nurul Jannah Lailatul Fitria (Borneo Research and Education Center, 2026)
This community service activity aims to address the problems faced by the partner regarding the management of broiler chicken farms in Gandasari, with the objective of increasing production and improving the quality of chicken meat. The activity is intended to enhance the understanding, skills, and interest of employees and young people in applying appropriate farm management practices, thereby increasing livestock production and improving its quality. This community service activity focuses on community participation techniques and was carried out in Gandasari Village, Majalengka Regency. The activity was conducted through extension sessions, practical exercises, and discussions, with the sessions designed to be interactive and engaging for the 30 participants involved. The results of the community service programme show that young people and livestock farm employees require extension activities on tips and techniques for producing high-quality broiler chickens in maximum quantities. Young people became more interested in entrepreneurship in the livestock sector, while employees were able to improve their skills in livestock farming processes. The activity also provided practical tips and explained the equipment used in broiler chicken farming. As a result, both the young people and the staff not only gained a better understanding but also became more skilled and enthusiastic. The evaluation results further confirmed that the partners require extension activities to be conducted on a gradual and sustainable basis.